Alterations of lung and gut microbiota in sodium butyrate alleviating heat stress-induced lung injury of broilers - Qiang Niu; Yiwen Lu; Meijuan Ren; Jiale Zhu; Yan Zhao; RuMeng Zhang; Xiaojun Yang; Qingzhu Sun (Poultry Science)
Heat-induced stress has a significant impact on the health of broilers. It induces panting behavior and elevates oxygen consumption, leading to considerable strain on the broiler lungs. However, the precise effects of heat stress on lung injury, along with changes in the lung and gut microbiota, are not yet fully understood. In our study, Arbor Acres (AA) broilers were employed as a model to assess the efficacy of sodium butyrate (SB) in mitigating heat stress-induced lung injury, while concurrently exploring the potential role of lung and gut microbiota in this phenomenon. Heat stress negatively affected broilers, particularly leading to lung injury, which was alleviated by dietary supplementation with SB. However, antibiotic-induced dysbiosis of the microbiota diminished the protective effects of SB, highlighting the critical importance of gut microbiota homeostasis. Heat stress resulted in a reduction in lung microbial diversity and altered its composition, primarily due to the depletion of g_Clostridia and the proliferation of g_Staphylococcus. SB supplementation helped restore beneficial microbes and improved their adaptation to heat stress. Heat stress induced comparable effects on the gut microbiota, resulting in a decline in p_Firmicutes and an elevation in p_Bacteroidetes. However, SB supplementation effectively modulated these alterations in the gut microbiota, promoting a more beneficial microbial profile. Our findings highlighted the significant contributions of both lung and gut microbiota in maintaining homeostasis during heat stress. Moreover, SB administration demonstrated its efficacy in mitigating heat stress-induced lung injury in broilers. This study provides critical insights for developing dietary strategies to reduce heat stress and promote broiler health.